Predictors of Bronchopulmonary Dysplasia in Infants With Birth Weight Less Than 1500 g - Galuh Martin Maytasari MD, MSc; Ekawaty Lutfia Haksari MD, MPH, PhD; Endy Paryanto Prawirohartono MD, MPH (SAGE Publishing, 2023)
Bronchopulmonary dysplasia (BPD) is a complication of preterm and low birth weight infants. The incidence of BPD has not decreased over the past 20 years. Complications of BPD include rehospitalization, chronic lung disease, cardiovascular disease, and impaired growth and development which will affect the patient's quality of life. There are unfortunately limited data available regarding BPD in Indonesia. This study is expected to be a reference in taking preventive measures to reduce mortality and morbidity in preterm and low birth infants. This study aims to determine predictors of BPD in infants with birth weight less than 1500 g. We conducted a retrospective cohort study that included 116 infants with birth weight <1500 g. Twenty-two (19%) infants had BPD with the highest proportion (63.6%) in the 28 to 31 weeks of gestational age. Multivariate analysis showed mechanical ventilation in more than first 2 days of life ( P  = .008; HR = 7.7), hematocrit <39% ( P  = .001; HR = 12), and hemodynamically significant patent ductus arteriosus (hsPDA; P  = .041; HR = 3.5) were significant predictors of BPD in infants with birth weight <1500 g.